Reducing agro-environmental trade-offs through sustainable livestock intensification across smallholder systems in Northern Tanzania - Birthe K. Paul; Jeroen C. J. Groot; Celine A. Birnholz; Beatus Nzogela; A. Notenbaert; Kassahun Woyessa; Rolf Sommer; Ravic Nijbroek; Pablo Tittonell (International Journal of Agricultural Sustainability, 2020)
Livestock productivity in East Africa, and especially in Tanzania, remains persistently low, while greenhouse gas (GHG) emission intensities are among the highest worldwide. This mixed methods study aims to explore sustainable livestock intensification options that reduce agro-environmental trade-offs across different smallholder farming systems in Northern Tanzania. A smallholder livestock systems typology was constructed, and representative farms simulated with a whole farm multi-objective optimization model. Livestock contributed more than 90% of on-farm GHG emissions, and DAIRY had the lowest GHG emission intensity (2.1 kg CO2e kg−1 milk). All livestock systems had alternative options available to reduce agro-environmental trade-offs, including reducing ruminant numbers, replacing local cattle with improved dairy breeds, improving feeding through on-farm forage cultivation, and minimizing crop residue feeding. Three obstacles to adoption of these technologies became apparent: they require a skillful re-organization of the entire production system, result in loss of some multi-functionality of livestock, and incur higher production risks. Sustainable livestock intensification can be a key building block to Tanzania's climate-smart agriculture portfolio, providing synergies between productivity and income increases, and climate change mitigation as co-benefit. A better understanding of the institutional settings, incentives and coordination between stakeholders is needed to sustainably transform the livestock sector.